Field test and analysis of the abnormal vibration of the medium-speed maglev train with mid-mounted linear motors. Issue 10 (3rd October 2021) - Liu, Yaozong; Wang, Shaoyi; Zhao, Shengquan; Xu, Hongping; Xu, Minglei
Abstract : In order to reveal the abnormal vibration of a newly developed 200 km/h medium-speed maglev vehicle with mid-mounted permanent magnet linear synchronous motors at specific speeds, field vibration tests at different running speeds are carried out and analysed in this paper. The accelerations of the linear motor and levitation module were measured during powered running as well as idle running. Data analysis indicates that the vertical and longitudinal forced resonance of the PMLSMs result in the abnormal vibrations. The idle running tests imply that the excitation force comes from the vertical attraction force between the permanent magnets of the motor and steel sleepers. These results point out the direction of dynamic optimisation of the bogie.